REKONSTRUKSI KESETARAAN DAN KEADILAN GENDER DALAM KONTEKS SOSIAL BUDAYA DAN AGAMA - Ch, Mufidah (EGALITA, 2006)
Gender study concerns with the effort to posit the women and men in equal position as a part of social system integratively. The aim of the effort is to eliminate gender equality which exists in society due to socio-cultural, political policies as well as religious doctrine interpretations factors. To realize this equal gender relation between men and women, gender analysis technique is used particularly in development process to assess the causes and the problems of unequal gender relation of both sexes. Thus, the result of analysisÂ  can be used as the considerations for women empowerment program to build up women's potentials that they can participate in development process together with men.